Decolonizing Justice: Indigenous Feminist Activism in Mary Kathryn Nagle’s Sovereignty - Riccetti, Sara (Review of International American Studies, 2024)
This article offers an analysis of the 2018 play Sovereignty by Cherokee playwright, lawyer, and activist Mary Kathryn Nagle. First performed at the Arena Stage Theatre in Washington DC, Sovereignty unfolds over two parallel timelines: present-day Oklahoma and the early 1800s in the southern Appalachians. In the present day, young Cherokee lawyer Sarah Ridge Polson and Cherokee Attorney General Jim Ross defend the inherent jurisdiction of the Cherokee Nation under the Violence Against Women Act in a pivotal case before the US Supreme Court. This modern struggle is juxtaposed with scenes from the 1800s, where their ancestors grapple with a proposed treaty with Andrew Jackson’s administration, leading to the signing of the Treaty of New Echota and the Trail of Tears. By juxtaposing historical and contemporary events, Nagle illuminates the enduring effects of government policies and laws that continue to render Indigenous people, particularly Indigenous women, vulnerable. This article explores how Sovereignty exemplifies Indigenous feminist literary activism through performative counter-storytelling, a method that enacts decolonization and reframes the stage as a critical space for asserting Indigenous performative sovereignty and self-determination. Using an Indigenous feminist literary critical approach, this article shows how Nagle constructs a counter-narrative that advances decolonization by addressing gendered outcomes of colonial law, challenging patriarchal cultural practices of misrepresentation, and embodying “radical relationality”—a concept of collective political organization based on principles of interdependency and responsibility. Through the character of Sarah Ridge Polson and her activism to restore sovereignty over her body and her nation, Sovereignty exemplifies Indigenous feminist activism through theater, reasserting Indigenous women as agents of cultural transmission and tribal values, illustrating that tribal sovereignty and gender empowerment are inherently interconnected and mutually reinforcing.